Technical aspects of neurostimulation: Focus on equipment, electric field modeling, and stimulation protocols. (June 2016) - Klooster, D.C.W.; de Louw, A.J.A.; Aldenkamp, A.P.; Besseling, R.M.H.; Mestrom, R.M.C.; Carrette, S.; Zinger, S.; Bergmans, J.W.M.; Mess, W.H.; Vonck, K.; Carrette, E.; Breuer, L.E.M.; et al.
Graphical abstract: Highlights: Neuromodulation is an emerging field with promising therapeutic possibilities. Incomplete understanding of mechanisms of action causes suboptimal clinical results. Knowledge of technical basis is necessary for deeper insight in these mechanisms. There are a lot of unsolved issues concerning optimal stimulation protocols. Abstract: Neuromodulation is a field of science, medicine, and bioengineering that encompasses implantable and non-implantable technologies for the purpose of improving quality of life and functioning of humans. Brain neuromodulation involves different neurostimulation techniques: transcranial magnetic stimulation (TMS), transcranial direct current stimulation (tDCS), vagus nerve stimulation (VNS), and deep brain stimulation (DBS), which are being used both to study their effects on cognitive brain functions and to treat neuropsychiatric disorders. The mechanisms of action of neurostimulation remain incompletely understood. Insight into the technical basis of neurostimulation might be a first step towards a more profound understanding of these mechanisms, which might lead to improved clinical outcome and therapeutic potential. This review provides an overview of the technical basis of neurostimulation focusing on the equipment, the present understanding of induced electric fields, and the stimulation protocols. The review is written from a technical perspective aimed at supporting the use of neurostimulation in clinical practice.